Tibetan medicine pain relieving plaster for treatment of knee osteoarthritis: protocol for a multi-center, randomized, and positive drug controlled trial - Yuan, Yi; Wang, Ying-jie; Guo, Ai; Wang, Wei-guo; Wang, Wei; Liu, Pei-lai; Shen, Zhi-xiu; Xie, Jian-rong; Liu, Kai-lie; Zhao, Min; Zuo, Jing-ling; Liu, Kai; et al. (Frontiers in Medicine, 2025)
ObjectiveThis trial aims to evaluate the effectiveness and safety of a Tibetan medicine pain relieving plaster (PRP) in knee osteoarthritis (KOA) management, generating evidence-based support for clinical application.MethodThis multi-center, randomized, positive drug-controlled, non-inferiority trial will evaluate the effectiveness and safety of the PRP in symptomatic participants with KOA. The trial will enroll 440 participants, allocated in a 1:1 ratio to the PRP group and flurbiprofen cataplasms group. All participants will undergo a 7-day treatment period followed by 14-day post-treatment monitoring. We will assess pain severity by the pain dimension score of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scale, and evaluate knee joint function using the stiffness and joint function dimension scores of the WOMAC scale and knee joint range of motion. We will assess joint swelling by measuring knee circumference. The quality of life will be evaluated using EQ-5D-5L scale, with utility scores calculated based on utility values and changes in the frequency of each level across dimensions. For safety assessment, we will perform blood laboratory tests, detailed recording of adverse events, and assessment of the severity of local skin reactions to the plaster based on a four-point Likert scale. In addition, we will record information related to plaster use, compliance, and the use of rescue therapy.DiscussionThis methodologically robust randomized controlled trial will comprehensively characterize PRP’s therapeutic potential in KOA management, specifically examining its impacts on core clinical manifestations (pain, mobility restriction, joint swelling) and patient-reported outcomes. The findings will inform evidence-based utilization of this approved Tibetan medicinal formulation in real-world clinical practice.